Impact of Blockchain Technology on Operational Performance of Ware housing (Logistics) Industry in Sri Lanka (Prakriti - The International Multidisciplinary Research Journal, 2025)
Blockchain is a next-generation technology evolvement in most industries in the world, such as logistics, financing, food, supply chain, etc. According to the literature, it was identified that warehousing companies face issues such as documentation, lengthy process lead time, intermediary involvement, lesser transparency in the processes, and bullwhip effect (demand and supply forecasting errors). Therefore, to reduce these risks it could adapt to the latest technologies, such as Blockchain technology organization wise. The primary objective behind this research is to identify the significant factors/ antecedent affecting the operational performance of Sri Lanka’s warehousing industry. Two latent variables that affect the operational performance of Sri Lankan warehouses have been discovered based on the literature review. The Independent Variable of this study is attributes of Blockchain technology and there are three dimensions identified: Decentralization (peer-to-peer network), Transparency (verified), and Computation logic (smart contracts). The warehouse’s operational performance serves as the dependent variable. This study’s population consists of employees who work at the warehouse/ transport service providing organization that is practicing blockchain technology local and multinational, employees, who work at the warehouse/ transport service providing organization that is not practicing the said technology local and multinational. A sample of three hundred and seventy (370) with a confidence level (95%) and margin of error (5%) has been utilized for analysis. This survey applied simple random sampling. The operation performance of the warehouse was significantly influenced by the variable network decentralization, despite the explanatory power of information transparency being rejected.
Keywords: Block Chain Tech nology; Computation Logic; Decentralization; Smart Contracts; Transparency